The impact of employment protection on the temporary employment services sector: Evidence from South Africa using data from tax records - Aalia Cassim (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
Attempts to regulate the temporary employment sector have had mixed results internationally. In South Africa, temporary employment was regulated in 2015 through amendments to the Labour Relations Act. This paper uses administrative data to examine the short-term impact of strengthening employment protection legislation in the temporary employment services (TES) sector, focusing on employment, job duration, and wages. A regression discontinuity design is used as the amendments applied only to employees earning below a certain threshold. The findings suggest that while working conditions improved for those that transitioned out of the TES sector into the non-TES sector, a larger proportion of individuals moved out of the data into informal employment, unemployment, or economic inactivity after the amendments were implemented. Providing empirical evidence on the impact of the amendments is an important contribution to the debate on regulating labour markets in developing countries, particularly in South Africa given its considerable unemployment rate.
Keywords: J31; J41; 330; administrative data; employment protection legislation; regression discontinuity design; South Africa; temporary employment services